Masculinity Construction in Apple Iphone 7 Plus Commercials: “The Rock X Siri – Dominate the Day and the Dive” - Nico Christiawan Untaryo (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This study is conducted to reveal the masculinity construction in the commercial of Apple iPhone 7 Plus The Rock x Siri – Dominate The Day and The Dive. The writer use Masculinity concept as a guideline and Gillian Dyer’s list the theory of human signs (1982) to examine the visual signs in both of the commercial videos. The elements that analyze are appearance, manner, and activity. In the analysis, the commercials show masculinity as having confidence, dedication and freedom. Confidence are shown from the appearance, manner and activity, Dedication and Free are shown from the activity. To conclude The Rock x Siri – Dominate The Day and The Divecan be a new reflections of today’s masculinity while promoting their product.